Pengaruh Proporsi Dewan Komisaris Independen, Komite Audit dan Audit Internal Terhadap Manajemen Laba Berbasis Akrual - Grace Fitri Angelica; Budi Kurniawan (UNIVERSITAS KALBIS, 2022)
This study is a quantitative study that aims to determine the effect of the proportion of independent commissioners from manufacturing companies, audit committees who have more ability in accounting for the management of company financial statements and whether internal audit has a close relationship with accrual-based earnings management as a moderating variable. The population in this study are all manufacturing companies. The number of research samples that have been obtained are 19 companies using purposive sampling method. The data analysis method used is path analysis using E-views 10. The results of this study indicate that the audit committee has a positive effect on earnings management in the company, the proportion of independent commissioners has no effect on company earnings management and internal audit has a negative effect on accrual basis earnings management as a variable. moderation. So that has a close relationship with the company's earnings management, namely the audit committee in reporting the results of the annual audit report on manufacturing companies